Engaging medical laboratory scientists in future pandemics: Lessons from the COVID-19 pandemic in Nigeria - Victor Chisom Makata; Moses Chukwuemeka Ekwebelem; Victor Godwin Essien; Fortune Benjamin Effiong (University of New South Wales, 2023)
The role of medical laboratory scientists has been critical in the early identification of the causative agent of the COVID-19 global pandemic, and the ongoing management and surveillance of the disease. Lessons from the Nigerian experience include the need to improve the capacity of laboratories in molecular diagnosis, increase the number of laboratories within the Nigerian Centre for Disease Control network, and establish more viral laboratories across the country. Keywords: COVID-19, infectious disease, health care reform, pandemic, medical laboratory scientist